2003
DOI: 10.1007/s00299-003-0611-z
|View full text |Cite
|
Sign up to set email alerts
|

Auxin deprivation induces a developmental switch in maize somatic embryogenesis involving redistribution of microtubules and actin filaments from endoplasmic to cortical cytoskeletal arrays

Abstract: A developmental switch from non-polar pre-embryogenic units to polarized transition units in maize embryogenic callus is caused by auxin deprivation from the culture medium. This switch is accompanied by cytoskeletal rearrangements in embryogenic cells. An immunofluorescence study revealed prominent endoplasmic microtubules and actin filament meshworks radiating from the nuclear surfaces in pre-embryogenic cells growing on medium supplemented with auxin. On the other hand, parallel-organized cortical microtubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
2
12
0
3
Order By: Relevance
“…These authors suggested that Dicamba has very rapid metabolism in wheat tissue, while Moore (1989) reported that 2,4-D is a highly stable auxin, showing strong resistance to enzymatic degradation and conjugation in plant cell. Exogenous auxin is needed to induce mitotic divisions of explant cells, but auxin deprivation is necessary for further progress of embryogenic morphogenesis (Sˇamaj et al, 2003). From this point, Dicamba presumably is more rapidly lost from callusinduction medium and callus tissue than 2,4-D, therefore germination of somatic embryos occurred earlier on medium supplemented with Dicamba.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that Dicamba has very rapid metabolism in wheat tissue, while Moore (1989) reported that 2,4-D is a highly stable auxin, showing strong resistance to enzymatic degradation and conjugation in plant cell. Exogenous auxin is needed to induce mitotic divisions of explant cells, but auxin deprivation is necessary for further progress of embryogenic morphogenesis (Sˇamaj et al, 2003). From this point, Dicamba presumably is more rapidly lost from callusinduction medium and callus tissue than 2,4-D, therefore germination of somatic embryos occurred earlier on medium supplemented with Dicamba.…”
Section: Discussionmentioning
confidence: 99%
“…Histological observations of the explants at different stages of regeneration provided evidence for the conversion of globular structures (globular stage embryos) into shoots. In embryogenesis, the preembryogenic units should be converted into transition units which are polarized structures composed of tightly arranged meristematic cells at the apical pole and suspensor-like elongated cells at the basal pole within a short time (Samaj et al 2003). Another distinctive feature of somatic embryos is the separation from the explant leading to the formation of a plantlet.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in medium containing auxins and cytokinins, the cells divide and produce calli, whereas when only auxins are present in medium, excessive cell elongation occurs and tubular structures appear [1]. A develop mental switch from nonpolar pre embryogenic units to polarized transition ones in maize embryogenic cal lus is caused by auxin deprivation from the culture medium; this switch is accompanied by cytoskeletal rearrangements in embryogenic cells [20]. In medium supplemented with auxins, long endoplasmic MTs and MF arrays radiated from the nuclear surfaces in pre embryogenic cells, what indicates cell embryogenic competence.…”
Section: Auxins and Microtubulesmentioning
confidence: 96%
“…At the same time, in the medium deprived of auxins, parallel organized cortical MTs and MFs associated with polarized embryogenic cells of transition units were present. Thus, a dynamic equi librium takes place between endoplasmic and cortical MTs and MFs, which is required for the realization of somatic embryogenesis under the influence of auxins and cytokinins [20].…”
Section: Auxins and Microtubulesmentioning
confidence: 99%